ANALISIS KONSUMSI PANGAN RUMAH TANGGA PASCA KRISIS EKONOMI DI PROPINSI JAWA BARAT - MEWA ARIANI; TRI BASTUTI PURWANTINI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Food is the most fundamental need for household, directly related to the quality ofhuman resources. The objective of this paper is to analyze the pattern of household foodconsumption in West Java province after economic crisis. Data are from SUSENAS year1996,1999 and 2002. The results are : 1) Prosperity level of households after economiccrisis is getting better, but it still lower than condition before crisis, 2) When theeconomic crisis happened, energy and protein consumptions of household decreased andthe slope of it in West Java province was higher than national level. After economiccrisis, consumption level of both nutrients then increase again, 3) Consumption of ricedecrease after crisis, but consumption of instant noodle increase. The pattern of staplefood consumption also change from rice pattern to rice-noodle pattern based of bothregion and income group. The implications of the policy is developing program of fooddiversification in the future must be implemented in more accurate way, supported bydeeper research about consumer behavior. Besides, efforts to increase purchasing powerand availability of some commodities such as animal foods, vegetables and fruits must bedone. In accordance with that, people awareness of food, nutrition and health must beincrease too. Political will and political power of governments are the success deciders.